2010
DOI: 10.3109/13685538.2010.529196
|View full text |Cite
|
Sign up to set email alerts
|

Association of shorter mean telomere length with large artery stiffness in patients with coronary heart disease

Abstract: The data show an association of leukocyte telomere length shortening with increased arterial stiffness and cardiovascular burden, suggesting that telomere length is a biomarker of large artery elasticity and CAD. Further studies are warranted to study the role of LTL dynamics in the pathogenesis of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
3
24
0
1
Order By: Relevance
“…The Sikh males had significantly shorter mean RTL compared to Sikh females, P =0.014. These findings are in agreement with several previous studies from multiple ethnic populations reporting presence of shorter RTL associated with age-related cardiometabolic diseases including T2D, insulin resistance, MI, and CHD 31,43, 44 , containing three previous studies on South Asians 12 , 21, 45 . We also report discovery of a novel signal represented by an intronic variant in CSNK2A2 gene associated with shorter RTL ( P =4.52×10 −8 ) in Punjabi Sikhs (Supplementary Figure 4).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Sikh males had significantly shorter mean RTL compared to Sikh females, P =0.014. These findings are in agreement with several previous studies from multiple ethnic populations reporting presence of shorter RTL associated with age-related cardiometabolic diseases including T2D, insulin resistance, MI, and CHD 31,43, 44 , containing three previous studies on South Asians 12 , 21, 45 . We also report discovery of a novel signal represented by an intronic variant in CSNK2A2 gene associated with shorter RTL ( P =4.52×10 −8 ) in Punjabi Sikhs (Supplementary Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, mean RTL showed a gradual decline from healthy subjects (with no disease) to individuals with T2D and CHD showing respective mean RTL of 2.67± 0.16 in healthy, 2.08±0.14 in CHD, 1.83±0.34 in T2D, and 0.77±0.14 in T2D+CHD individuals showing highly significant difference between healthy subjects versus T2D and CHD patients ( P =3×10 −15 ) (Figure 5). Mean RTL levels were also significantly lower ( P =0.014) in Sikh males (1.82±0.11) compared with females (2.29±0.15), irrespective of the disease status, consistent with observations in South Asians and other ethnic groups 21, 31, 43, 44 (Supplementary Figure 2). …”
Section: Resultssupporting
confidence: 85%
“…Furthermore, cross-sectional studies have shown that a shorter TL is associated with measures of vascular stiffness, including increased aPWV and reduced carotid distensibility (Benetos et al 2001;Nawrot et al 2010;Wang et al 2011). However, other cross-sectional studies have reported no association between TL and arterial stiffness in females (Benetos et al 2001) and in diabetics (Tentolouris et al 2007).…”
Section: Mcdonnellmentioning
confidence: 99%
“…Two recent meta-analyses have demonstrated that telomere shortening is related to CV (Haycock et al 2014) and metabolic outcomes (D'Mello et al 2015), although there was significant heterogeneity in observations within these studies. Interestingly, previous studies have also reported significant cross-sectional associations between TL and measures of vascular stiffness (Benetos et al 2001;Nawrot et al 2010;Wang et al 2011) and a recent longitudinal study illustrated that a faster rate of telomere shortening was associated with increased carotid intima-media thickness, independent of traditional CV risk factors (Masi et al 2014), leading to the hypothesis that telomere shortening provides a cellular and genetic link to vascular ageing. However, observational studies conducted mostly in middle-aged and older adults have shown weak or no relationship between TL and chronological age, vascular stiffness or CV disease (Tentolouris et al 2007;De Meyer et al 2012;Morgan et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have suggested relationships between telomere length and cardiovascular diseases, although the associations varied across studies [34][35][36][37][38], while associations between the misregulation of telomere length and diabetes have also been reported [39][40][41].…”
mentioning
confidence: 99%